Control financiero de la procesadora "María Martínez" del cantón Baba año 2020-2021. - López Delgado, Zulay Dolores (2022)
Financial control is a fundamental part of financial management that must be taken into account in any organization, regardless of its type or composition. Its importance is appreciated seeing it from the basic point of view of the action of managing within the organization itself, planning cannot be developed without carrying out control; there can be no organizing process without control; There can be no obtaining of human, material and financial resources without proper control and it cannot be managed without control. That is why the present investigation is aimed at giving clear and exact information about what a financial control system is, the same one that will help us to obtain an adequate control of all the operations and financial information carried out in the processor. In the "María Martínez" processor of the Baba canton, no financial control system has been carried out, so the elaboration of this case study will be a novel event within the company since it will allow acquiring more knowledge on the subject, which It will be very helpful to achieve greater efficiency in terms of obtaining and presenting adequate, timely and, above all, reliable financial information that will allow the manager to make appropriate decisions. This will strengthen the optimal management of the processor's resources, which that would guarantee sustained growth based on a greater amount of income.